2005
DOI: 10.1111/j.1600-0447.2004.00440.x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Bech–Rafaelsen Melancholia Scale and the Hamilton Depression Scale in patients with major depression; is the total score a valid measure of illness severity?

Abstract: The HAM-D(6) and the MES did fulfil criteria for unidimensionality while the HAM-D(17) did not. Therefore, the extended use of the HAM-D(17) in drug trials may be questioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
93
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(100 citation statements)
references
References 23 publications
3
93
0
2
Order By: Relevance
“…The subscale defined by these six items is now commonly referred to as 'Hamilton-6' (HDRS 6 ) (5). As opposed to the HDRS, the psychometric validity of the HDRS 6 has been confirmed numerous times (8)(9)(10)(11)(12)(13)(14)(15) since its derivation from the HDRS in 1975 (6). Importantly, when using the total score on the HDRS 6 as outcome measure in RCTs of SSRIs (and related antidepressants) versus placebo, the effect sizes are markedly larger than those obtained when using the total score of the HDRS as outcome measure (17)(18)(19)(20).…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…The subscale defined by these six items is now commonly referred to as 'Hamilton-6' (HDRS 6 ) (5). As opposed to the HDRS, the psychometric validity of the HDRS 6 has been confirmed numerous times (8)(9)(10)(11)(12)(13)(14)(15) since its derivation from the HDRS in 1975 (6). Importantly, when using the total score on the HDRS 6 as outcome measure in RCTs of SSRIs (and related antidepressants) versus placebo, the effect sizes are markedly larger than those obtained when using the total score of the HDRS as outcome measure (17)(18)(19)(20).…”
mentioning
confidence: 91%
“…In two landmark studies from 1975 (6) and 1981 (7), respectively, Bech et al demonstrated that the original HDRS met none of these two criteria. This lack of psychometric validity of the HDRS has been confirmed in a large number of studies since then (8)(9)(10)(11)(12)(13)(14)(15). Therefore, the total score of the HDRS cannot be considered as a clinically valid measure of the severity of depression (5,16).…”
mentioning
confidence: 99%
“…In addition, the 17-item version has also been shown to measure more than one dimension. 58 The Ham-D is available in the public domain (see, for example, Table 3 located in Supplementary Material) and has been translated into most European and Asian languages. There are self-rated and over the telephone-administered formats that yield comparable results to the intervieweradministered version.…”
Section: Depression In Non-pd Patientsmentioning
confidence: 99%
“…69,70 More recently there has been a surge of interest in IRT for quality of life and related constructs. Papers advocating the use of IRT in health outcome measurement include Revicki and Cella 71 and Hays et al 72 in Quality of Life Research and Medical Care, respectively, journals that regularly publish papers using IRT.…”
Section: Some Applications Of Irt In Medical Researchmentioning
confidence: 99%